Uso de macroalgas e variáveis físicas, químicas e biológicas para a avaliação da qualidade da água do Rio do Monjolinho, São Carlos, Estado de São Paulo - Peres, Ana Claudia (2002)
A fluvial ecosystem has a big interaction surface with the terrestrial ecosystems. The river interact with the terrestrial ecosystem, in drains, in an equilibrated and functional unit. Besides being is a low tension system, that is overloaded and that exports part of its materials, it keeps a quick cycle. Macroalgae are benthic organisms that produce a mature stalk, that has a discreet structure, however recognized by naked eye. Those algae have been used for river monitoring, in Europe particularly, as biological indicators and they are better than the physical and chemical variables, that reflects only the water conditions in the collecting moment, whereas the biological indicators reproduce medium-long term aspects of living organisms. This study has as principal aiming, was to establish a relationship between the macroalgae species found and the ambiental variables at the Monjolinho River, tracing a water quality profile of this river. The study was performed in 6 months (May to October, 1998 dry season) in six sampling stations distributed along all the river extension. During six months sampling were performed in a six stretch of 10m along to the river course. Water was collected for nutrient and suspended matter analyses and measurements of variables as, water temperature, conductivity, pH, turbidity and dissolved oxygen. Macoralgae were samples qualitatively and quantitatively. A total of 16 sampling macroalgae species present, among which Vaucheria geminata, Schysomeris leibleinii, Geithlerinema amphybium and Stigeoclonium helveticum had a wide distribution. In relation to the ambiental variables, the station was found to have the lowest nutrient concentration and highest OD, whereas the station 3 had the highest nutrient concentration and lowest OD concentrations. The sampling stations were classified, according to the values of BOD, saturation oxygen deficit, NH4, and OM as: station 1 Oligossaprobic (health water zone, not affected by the pollution ), station 2 and 6 â-mesossaprobic (zone of lightly weak pollution), station, 4 and 5 á-messoproibic (polluted zone or strongly polluted) and station 3 polissaprobic (extremely polluted zone or intense bacterial decomposition).